Metabotropic Glutamate Receptors as Novel Therapeutic Targets on Visceral Sensory Pathways - Blackshaw, L. Ashley (Frontiers Research Foundation, 2011)
Metabotropic glutamate receptors (mGluR) have a diverse range of structures and molecular coupling mechanisms. There are eight mGluR subtypes divided into three major groups. Group I (mGluR1 and 5) is excitatory; groups II (mGluR2 and 3) and III (mGluR 4, 6, and 7) are inhibitory. All mGluR are found in the mammalian nervous system but some are absent from sensory neurons. The focus here is on mGluR in sensory pathways from the viscera, where they have been explored as therapeutic targets. Group I mGluR are activated by endogenous glutamate or constitutively active without agonist. Constitutive activity can be exploited by inverse agonists to reduce neuronal excitability without synaptic input. This is promising for reducing activation of nociceptive afferents and pain using mGluR5 negative allosteric modulators. Many inhibitory mGluR are also expressed in visceral afferents, many of which markedly reduce excitability. Their role in visceral pain remains to be determined, but they have shown promise in inhibition of the triggering of gastro-esophageal reflux, via an action on mechanosensory gastric afferents. The extent of reflux inhibition is limited, however, and may not reach a clinically useful level. On the other hand, negative modulation of mGluR5 has very potent actions on reflux inhibition, which has produced the most likely candidates so far as therapeutic drugs. These act probably outside the central nervous system, and may therefore provide a generous therapeutic window. There are many unanswered questions about mGluR along visceral afferent pathways, the answers to which may reveal many more therapeutic candidates.